Close to earth : an observational documentary portrait - Gunasegaran, Shammini (2016)
Close to Earth: An Observational Documentary Portrait, is a detailed personal report that introduces, contextualises and describes the development of the film. It surveys the film's influences and evaluates the decisions made throughout the production.